Changes in Life History Traits of Small Pelagic Fish in the Western Mediterranean Sea - Albo-Puigserver, Marta; Pennino, Maria Grazia; Bellido, Jose María; Colmenero, Ana Isabel; Giráldez, Ana; Hidalgo, Manuel; Gabriel Ramírez, John; Steenbeek, Jeroen; Torres, Pedro; Cousido-Rocha, Marta; Coll, Marta (Frontiers in Marine Science, 2021)
Small pelagic fish (SPF) in the western Mediterranean Sea are key elements of the marine food web and are important in terms of biomass and fisheries catches. Significant declines in biomass, landings, and changes in the age/size structure of sardine Sardina pilchardus and anchovy Engraulis encrasicolus have been observed in recent decades, particularly in the northern area of the western Mediterranean Sea. To understand the different patterns observed in SPF populations, we analyzed key life history traits [total length at age, length at maturity, gonadosomatic index (GSI), and body condition (Kn)] of sardine and anchovy collected between 2003 and 2017, from different fishing harbors distributed along a latitudinal gradient from northern to southern Spain. We used Generalized Linear Models (GLM) to estimate the length at maturity and Generalized Additive Models (GAMs) to test the relationship with environmental variables (seawater temperature, water currents, and net primary productivity). The life history traits of both species presented seasonal, interannual and latitudinal differences with a clear decline in length at age, length at first maturity, and body condition, for both species in the northern part of the study area. In the southern part, on the contrary, life history traits did not present a clear temporal trend. The environmental conditions partially explained the long-term changes in life history traits, but the selected variables differed between areas, highlighting the importance of regional oceanographic conditions to understand the dynamics of small pelagic fish. The truncated length-at-age pattern for both species with the disappearance of the larger individuals of the population could have contributed to the poor condition of small pelagic fish populations in the northern part of the western Mediterranean Sea in recent years. In the south area, recent declines in body condition for sardine and anchovy were observed and could be a possible first sign for future population declines. This study highlights the importance of understanding the trade-off between the energy invested in reproduction, maintenance and growth at seasonal and interannual level to advance our knowledge on how environmental and human pressures influence population dynamics of small pelagic fish at local and regional scales.